The good girl - Kubica, Mary (Mira Books, 2014)
The daughter of a prominent Chicago judge and his socialite wife, inner-city art teacher Mia Dennett is taken hostage by her one-night stand, Colin Thatcher, who, instead of delivering her to his employers, hides her in a secluded cabin in rural Minnesota to keep her safe from harm.